Roxadustat on Renal Anemia with Macroinflammation: A Retrospective Cohort Study - Yan Tu; Zuo-Lin Li; Hong Liu; Ri-Ning Tang; Gui-Hua Wang; Lin-Li Lv; Bin Wang; Bi-Cheng Liu (Karger Publishers, 2024)
Introduction: Roxadustat, the first-in-class drug for the treatment of renal anemia, has demonstrated efficacy in renal anemia with microinflammation. Additional data are needed regarding the efficacy of roxadustat on renal anemia with systemic macroinflammation. Methods: Three cohorts of renal anemia based on the basic level of high-sensitivity CRP were included. Patients with hsCRP ≤2 mg/L were selected as non-inflammation (NI) group; 2< hsCRP ≤10 mg/L as microinflammation (MI) group; hsCRP≥10 mg/L as macroinflammation (MA) group. Patients received oral roxadustat three times per week for 52 weeks. The primary end point was the hemoglobin level over weeks 12-52. The second end point was the cumulative proportion of patients achieving hemoglobin response by the end of week 12. Results: A total of 107 patients with chronic kidney diseases (CKDs) were enrolled. Overall, the baseline hemoglobin level of patients was 79.99 ± 11.20 g/L. Roxadustat could significantly increase the hemoglobin level in all of the three groups and did not show any significant difference (p > 0.05, respectively). Meanwhile, compared with that of the NI group, there was no significant difference in hemoglobin response rate in the MA group both at week 12 (p = 0.06; 95% confidence interval [CI], 0.9531-13.75) and week 52 (p = 0.37; 95% CI, 0.5080-7.937). Moreover, the hemoglobin response was independent of baseline hsCRP level (p = 0.72, 95% CI, −0.1139 to 0.0794). More importantly, roxadustat significantly reduced ferritin and serum iron levels and increased total iron-binding capacity in the three groups, which showed no significant differences among the three groups (p > 0.05, respectively). Conclusion: Roxadustat significantly improves anemia in CKD patients with systemic macroinflammation.